Noninvasive penetration of 5 nm hyaluronic acid molecules across the epidermal barrier (in vitro) and its interaction with human skin cells. Issue 1 (21st August 2017) - Nashchekina, Yu. A.; Raydan, M.
Abstract: Objective: Hyaluronic acid represents one of the major components of the extracellular environment. The main challenge remains in the ability to deliver these molecules noninvasively across the skin barrier, which can be overcome by the reduction in size to an extent that allows these molecules to pass across the skin barrier. The aim of this study was to measure the penetration and bioavailability of low molecular weight hyaluronic acid to cross an epidermal barrier model. Methods: Determining the quantity of hyaluronic acid in the test solutions was carried with method of photocolorimetry analysis. Investigation of the interaction of cells with LMWHA was studied with a confocal microscope. Results: The study showed that LMWHA is able to cross the epidermis. Most effective penetration level is during the first 6 hours reaching 75%, and then the concentration started to decline and reached the equilibrium state within the following 2 hours. Confocal laser microscopy demonstrated different distribution and behavior of these molecules among the keratinocytes and fibroblasts. Conclusion: Reducing the size of hyaluronic acid to 5 nm enhance their transport across the epidermal layer. The concentration of hyaluronic acid molecules was higher on the fibroblast surface in comparison to their extracellular environment.